Impact of Team Teaching on Student Teachers' Professional Identity: A Bayesian Approach - Loan De Backer; Wouter Schelfhout; Mathea Simons; Ellen Vandervieren; Jose Rivera Espejo (MDPI AG, 2023)
Workplace learning in teacher education is essential for creating and recreating the professional identity of student teachers. Innovative interventions, such as team teaching between student teachers and mentors at the workplace, are assumed to facilitate learning to teach. This experimental study provides valuable insight into the impact of team teaching on student teachers' professional identity by implementing distinct student teaching formats: team teaching (A1intervention), team teaching with support (A2intervention), and traditional teaching (Control intervention). In this study, professional identity is understood as a multidimensional concept that consists of six components: student teachers' learning and regulation activities, reflective thinking, teacher efficacy, beliefs about learning and teaching, motivation, and collaborative activities. A total of 464 student teachers from a Flemish College of Education were randomly assigned to one of the three student teaching formats. The overall findings of Bayesian structural equation modeling reveal significant impacts of team teaching with support compared to both team teaching and traditional teaching as well as a significant impact of team teaching over traditional teaching on three crucial components of student teachers' professional identity, i.e., their learning and regulation activities, reflective thinking, and motivation.